Surface characteristics of low temperature hybrid thermochemical treatment of AISI 316L - Triwiyanto, A. (American Institute of Physics Inc., 2015)
This investigation proposed the low temperature thermochemical treatments in conventional tube furnace of hybrid treating which introduces nitrogen and carbon simultaneously with the aim to improve surface properties of AISI 316L. The outcome of the work showed the formation expanded austenite structured which is supersaturated with nitrogen and carbon. This structure is responsible to the higher hardness as well as better wear property without impairing its corrosion resistance. Characterization of this expanded austenite layers were performed including FESEM, USPM and elemental analysis to reveal the characters of the produced thin layers. Elemental profile of nitrogen and carbon across the hybrid treated layer were obtained by EDS-SEM. The results also demonstrate that hybrid treatment produces a thicker and unique layer on higher temperature treatments for 450Â°C without impairing its corrosion resistance according to the absence of nitride and carbide of treated layers. Â© 2015 AIP Publishing LLC.